EKSISTENSI TOKOHHPEREMPUAN DALAMM NOVEL PEREMPUAN BERKALUNG SORBAN KARYAAABIDAH ELLKHALIEQY - Sapia, Siti; Takko, AB; Kuswarini, Prasuri (Universitas Hasanuddin, 2022)
This study aims to see how the female character exists in the novel Perempuan Berkalung Sorban by ABidah El Khalieqy. The data collection method used in this research is the literature study method. The data analysis method used in this research is the descriptive qualitative method. The types of data that will be used in this study are divided into two, namely data relating to the existence of female characters. The results of the study show that there are three ways of existence of female figures, namely, fighting against the rules that oppress women, becoming an educated woman, and upholding the rights and roles of women.